THE ECONOMIC AND SOCIAL BENEFITS OF AIR TRANSPORTATION TO TOURISM IN NIGERIA - Abdullahi, Mohammed Awwal; Adesogan, Adeniyi Adeola; Alhaji, Abdullahi Garba (PEOPLE: International Journal of Social Sciences, 2018)
The increasing accessibility of air flight has significantly widened air industry’s role in our contemporary social settings. As aircraft is no more an expensive valuable but rather a necessity. The aviation sector has not only support wealth generation in the advanced nations, but has also bought humongous impacts to advanced industrialization by tapping their endowment for business and tourism .The paper has kept us informed on about economic and social impact of aviation industry to tourism and its immensely offers to employment opportunities and Gross Domestic Products (GDP).As this information will furnish government and the aviation sector to take better steps to make sure air travel is continuous and tourism remains indefinite. Also other sectors are valuable to economical welfare of a country as air industry. Transportation is a main reason in forming people’s Social, Economic and Cultural reality by globalization. Aviation sector is currently rate as the principal resources of forming one whole economies and cultures and encourages social and cultural harmony, educational experience, industrial growth and variety in a rising reliant world community. The industrial community largely relies on safe reliable and agreeable priced. The industry is environmentally/friendly and responsible which has led to one of the highest benefactor to the development of our contemporary settings having addressed growing demand for mobility. Desk research methodology was used in reviewing the materials while the objectives is to highlight economic and social impacts of aviation industry to tourism, the findings are air industry has created millions of jobs Directly, indirectly and induced impacts which has led to industrialization.